Sustainable lean supply chain to minimize waste in solar water heater production - Emelia Sari, Emelia Sari; Amran, Tiena Gustina; Takari, Kinanti Mutiara; Akbari, Annisa Dewi; Raja Mamat, Tengku Nur Azila
The Solar Water Heater Production company is dedicated to manufacturing and supplying new and renewable energy. However, the company needs help in meeting its production targets. This research aims to address this issue by improving the supply chain flow by implementing a sustainable lean supply chain. The research process involves several steps: 1) identifying gaps in activities within the supply chain flow through value chain analysis, 2) determining the types of waste, 3) constructing an Ishikawa Diagram, 4) calculating the Sustainability Index (SI), and 5) implementing improvements. The research results indicate a 10% increase in process cycle efficiency after implementing improvements. Additionally, process activity mapping identified eight movements, 34 instances of waiting, five defects, and five behavioural activities. The calculation of the SI also showed improvement, improving from 142% to 121%. In conclusion, the research approach has successfully reduced waste and enhanced production efficiency. It has been achieved by integrating economic, social, and environmental factors into the improvement process, leading to successful manufacturing practices